Semantic web for the working ontologist modeling in RDF, RDFS and OWL - Allemang, Dean.; Hendler, James A. (Amsterdam ; Boston : Morgan Kaufmann Publishers/Elsevier, 2008)
The promise of the Semantic Web to provide a universal medium to exchange data information and knowledge has been well publicized. There are many sources too for basic information on the extensions to the WWW that permit content to be expressed in natural language yet used by software agents to easily find, share and integrate information. Until now individuals engaged in creating ontologies-- formal descriptions of the concepts, terms, and relationships within a given knowledge domain-- have had no sources beyond the technical standards documents. Semantic Web for the Working Ontologist transforms this information into the practical knowledge that programmers and subject domain experts need. Authors Allemang and Hendler begin with solutions to the basic problems, but don't stop there: they demonstrate how to develop your own solutions to problems of increasing complexity and ensure that your skills will keep pace with the continued evolution of the Semantic Web. . Provides practical information for all programmers and subject matter experts engaged in modeling data to fit the requirements of the Semantic Web. . De-emphasizes algorithms and proofs, focusing instead on real-world problems, creative solutions, and highly illustrative examples. . Presents detailed, ready-to-apply "recipes" for use in many specific situations. . Shows how to create new recipes from RDF, RDFS, and OWL constructs.
1 WHAT IS THE SEMANTIC WEB? -- 2 SEMANTIC MODELING -- 3 RDF -- THE BASIS OF THE SEMANTIC WEB -- 4 SEMANTIC WEB APPLICATION ARCHITECTURE -- 5 RDF AND INFERENCING -- 6 RDF SCHEMA LANGUAGE -- 7 RDFS-PLUS: -- 8 USING RDFS-PLUS IN THE WILD -- 9 BASIC OWL -- 10 COUNTING AND SETS IN OWL -- 11 USING OWL IN THE WILD -- 12 GETTING STARTED ON A MODEL -- GOOD AND BAD MODELING PRACTICES -- 13 OWL LEVELS AND LOGIC -- 14 CONCLUSIONS -- 15 FREQUENTLY ASKED QUESTIONS.
Includes bibliographical references (p. 317-320) and index.
Keywords: Web site development; Metadata; Semantic Web; Electronic books